The contribution of passive drag as a determinant of swimming performance - Chatard, J. C.; Lavoie, J. M.; Bourgoin, B.; Lacour, J. R. (International Journal of Sports Medicine, 1990)
This investigation represented a rekindling of interest in passive drag (the amount of drag measured on a stable object moving through water - such as a swimmer being towed). It is considered to be a good measure of gliding aptitude (streamlining potential). Active drag (alterations in drag that occur due to the activity and its various positional requirements) has also been of interest. Original active drag estimates seem to have been overestimated. Since passive drag is easier to measure and important particularly for breaststroke, it represents an important component of swimming. Passive drag, a 400 m swim, anthropometrical features, and VO2max in male and female trained swimmers were measured. Two other groups were formed to evaluate expiration and joint laxity. Performance over 400 m was highly related to VO2max, approximately 50% in both sexes. It is incorrect to assume that similar relationships also exist with shorter sprint distances. When passive drag values were added, prediction capabilities increased to over 60%. Passive drag is a significant factor in 400 m swimming. Both variables are even better predictors (over 70%) of performance over the last 40 m of a 400 m swim (they measure an individual's physical capacity to finish a race in a more economical manner). Passive drag was also related to a swimmer's surface area (males r = .8; females r = .58). It was also increased by 34% after maximum expiration. This means that passive drag is also influenced by body shape. Passive drag was also decreased in swimmers who have greater flexibility (joint laxity). Implications: Reductions in body surface area should be associated with reductions in passive drag. This might be a justification for advocating less body fat in swimmers. Caution must be exercised for this reasoning. Lean swimmers sink lower in the water because of increased specific density and may also alter the smoothness of contour lines because of angular delineations of muscles. However, it is reasonable to assume that excessive fat will increase surface area above a level supported by an optimal body shape. Increased flexibility will also contribute to a reduction in passive drag probably because the streamline posture of the body can be increased. It would seem that passive drag is a measure that should be included in swimmer assessments for it will indicate beneficial or detrimental changes in a body shape.